Measuring isoplanaticity in high-resolution electron microscopy - Meyer, R; Kirkland, A (2004)
We recently reported on a new method for the accurate determination of the symmetric aberration coefficients (defocus and twofold astigmatism) from a focal series of high resolution images based on an analysis of the image Fourier transform phases. This can be extended to also cover the antisymmetric aberrations (axial coma and three-fold astigmatism) by recording a combined tilt-focal series where at each beam tilt a short focal series of three images is recorded. In this paper we apply this method to investigate the variation of the wave aberration function coefficients across the field of view by an aberration measurement for an array of 7x7 independent subregions. For some datasets, a very significant variation of the axial coma was found, consistent with a convergence of the incident illumination that leads to a mistilt of up to 1 mrad at the borders of the field of view. This shows that the setting up of truly parallel illumination is important and difficult. No significant variations were found in the other aberration parameters. The non-parallelity of the illumination can also be assessed by measuring the focus-induced change in the magnification, and a good agreement was found between the two methods.